(untitled) (Global Journal of Human-Social Science, 2020)
The city of Rio do Sul, State of Santa Catarina, Brazil, is marked since its colonization in the last years of the 19th century from frequent and intense floods that shaped its urbanization and relation of its residents with the environment. After the 1983 floods that reached the historical record of 13.56 meters over the riverbed and the 2011 events, the second-highest ever, researchers argued that the local, territorial dynamics of spatial segregation and real estate market changed and became attached to the floods quotas. However, none of them ever showed these conclusions by empirical data, what is the objective of this research. After collecting data from 200 terrain properties to sale on this city, the researchers applied geostatistical (specially kriging) and geoprocessing methods with Geographic Information Systems to identify if there is a relation of cause-effect with the different flood quotas reaching the properties with its market value. The results are that this association exists, but is not the only variable that explains value variations in Rio do Sul, with relevant weight from the city’s centrality to real estate market prices.